1994
DOI: 10.1007/bf00203696
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of occult fractures of the proximal femur

Abstract: The evaluation of the painful hip in the elderly osteoporotic patient with normal plain radiographs can be difficult. We studied 15 osteopenic patients with normal plain radiographs and suspected hip fractures with magnetic resonance (MR) imaging and found MR to be an excellent aid in detecting occult fractures. A clear fracture was seen in 10 of the 15 patients, who then underwent surgical repair based on the MR study. The remaining patients had no MR-demonstrable fracture and were successfully treated nonope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…Other factors that may weaken bone include smoking, inactivity, rheumatoid arthritis, post-gastrectomy syndrome, a low percentage of body fat, poor calcium intake, excessive alcohol intake, and endocrine disorders such as diabetes, hyperthyroidism, hyperparathyroidism, and hypercortisolemia (24). Alcoholism as a factor in osteoporosis was seen in a 45-year-old-patient found to have occult hip fracture in Haramati et al's study (28).…”
Section: Osteoporosis Riskmentioning
confidence: 96%
“…Other factors that may weaken bone include smoking, inactivity, rheumatoid arthritis, post-gastrectomy syndrome, a low percentage of body fat, poor calcium intake, excessive alcohol intake, and endocrine disorders such as diabetes, hyperthyroidism, hyperparathyroidism, and hypercortisolemia (24). Alcoholism as a factor in osteoporosis was seen in a 45-year-old-patient found to have occult hip fracture in Haramati et al's study (28).…”
Section: Osteoporosis Riskmentioning
confidence: 96%
“…This approach has been reported by several authors elsewhere [4,12,15,18,20,22,24]. The study design allowed, to the best of our knowledge, for the first time a calculation of the interobserver variability (two radiologists for both methods) and an ROC analysis.…”
Section: Discussionmentioning
confidence: 98%
“…High-field MRI as well as low-field MRI systems have shown their diagnostic potential for the detection of musculoskeletal disorders and radiographically oc- Sensitivity, specificity, and accuracy were calculated as the mean of the results of both readers cult fractures [1,2,5,12,13,14,15,16,17,18,19,20,21]. The combination of STIR and T1-weighted sequences seems to allow a satisfactory evaluation of osseous lesions along with low-field MRI [9,22,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…25 Meanwhile, another study reported a 4.2% incidence, which was derived by dividing the number of occult operative hip fractures found by the total number of patients with operative hip fractures diagnosed during their study period. 26 Although magnetic resonance imaging (MRI) is universally recognized as the gold standard for diagnosing the occult hip fracture, 13,27 with sensitivity and specificity approaching 100%, 20,[28][29][30][31] earlier studies used either clinical progression or bone scanning for diagnosis. 19,[22][23][24] Bone scanning, or bone scintigraphy, has a reported sensitivity and specificity of 93% and 95%, respectively 32 ; however, it is thought to take 24 to 72 hours for a scan to become positive in older patients.…”
Section: Discussionmentioning
confidence: 99%